Setting of an import tolerance for pyraclostrobin in rice. (15th November 2018) - ,; Anastassiadou, Maria; Brancato, Alba; Brocca, Daniela; Carrasco Cabrera, Luis; De Lentdecker, Chloe; Erdos, Zoltan; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kardassi, Dimitra; Leuschner, Renata; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant BASF SE submitted a request to the competent national authority in Germany to set an import tolerance for the active substance pyraclostrobin in rice. The data submitted in support of the request were found to be sufficient to derive a maximum residue level (MRL) proposal for rice. Based on the risk assessment results, EFSA concluded that the short‐term intake of residues resulting from the use of pyraclostrobin according to the reported agricultural practices is unlikely to present a risk to consumer health. Taking into account the proposed new MRL, a long‐term intake concern for consumers was not identified.